2008
DOI: 10.1101/gad.460708
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitins control cell proliferation and apoptosis by regulating OPA1-dependent cristae morphogenesis in mitochondria

Abstract: Prohibitins comprise an evolutionarily conserved and ubiquitously expressed family of membrane proteins with poorly described functions. Large assemblies of PHB1 and PHB2 subunits are localized in the inner membrane of mitochondria, but various roles in other cellular compartments have also been proposed for both proteins. Here, we used conditional gene targeting of murine Phb2 to define cellular activities of prohibitins. Our experiments restrict the function of prohibitins to mitochondria and identify the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
557
4
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 486 publications
(614 citation statements)
references
References 58 publications
49
557
4
4
Order By: Relevance
“…These data suggest that PHB2 can inhibit mitochondrial fission and apoptosis, and PHB2 may antagonize myocardial injury. Previous reports have shown that loss of prohibitins results in the fragmentation of the mitochondrial network in HeLa cells and MEFs 13,14 . The mitochondrial fragmentation of PHB2-depleted MEFs strikingly resembles the mitochondrial morphology observed after OPA1 downregulation 14,27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggest that PHB2 can inhibit mitochondrial fission and apoptosis, and PHB2 may antagonize myocardial injury. Previous reports have shown that loss of prohibitins results in the fragmentation of the mitochondrial network in HeLa cells and MEFs 13,14 . The mitochondrial fragmentation of PHB2-depleted MEFs strikingly resembles the mitochondrial morphology observed after OPA1 downregulation 14,27 .…”
Section: Discussionmentioning
confidence: 99%
“…PHB2 has a predominantly mitochondrial function and it is related to mitochondrial network and apoptosis 26 . Deletion of PHB2 leads to an aberrant cristae morphogenesis and an impaired cellular proliferation and resistance towards apoptosis 14 . This suggests that PHB2 may have an important role in regulating mitochondrial morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PHB2 knockout resulted in early embryonic lethality (Park et al 2005), while PHB2 deletion impaired mouse embryonic fibroblast proliferation and increased their susceptibility to apoptotic stimuli (Merkwirth et al 2008). In breast cancer cells, nuclear PHB2 repressed the activity of estrogen receptor-α ).…”
Section: Prohibitin-2mentioning
confidence: 99%
“…Pro-oncogenic alterations in MEK/ERK signalling pathway lead to phosphorylation of Mfn-1, increasing its affinity to and sequestering Bax, so preventing apoptosis [53]. In some human colon cancer cell lines, it has been shown that Drp1 favours tumor growth, since its depletion reduces Opa-1-L to Opa-1-S ratio, thereby promoting cytC release from the cristae and apoptosis [54].…”
Section: Mitochondria-shaping Proteins In Apoptosismentioning
confidence: 99%